Hubungan Tingkat Asupan Gisi, Aktivitas Fisik, dan Motivasi Terhadap Tingkat Kebugaran Jasmani Siswa Usia 10-12 Tahun di SD NegeriKecamatan Jati Kudus - Alya Ega Suciana; Mugiyo Hartono; Cahyo Yuwono; Siti Baitul Mukarromah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the factors that influence the physical fitness of elementary school students, particularly the relationship between nutritional intake levels, physical activity, and learning motivation with students’ physical fitness. The background of this study is the increasing inactivity in physical activities, the low nutritional status and physical fitness test results, and the reduced duration of physical education (PJOK) lessons at the elementary school level. The method used was a quantitative approach with a correlational research design to analyze the relationship between nutritional intake levels, physical activity, and motivation toward students’ physical fitness. Data were collected using questionnaires and physical fitness tests. The population and sample consisted of 350 students from seven public elementary schools in Jati District, Kudus Regency. The sampling technique used in this study was purposive sampling. The results showed that: (1) the relationship between nutritional intake levels and physical fitness was not significant (p = 0.204), where the average nutritional intake was in the “moderate” category with a total of 265.8 kcal, far below the daily requirement of 500 kcal; (2) there was a significant relationship between physical activity and physical fitness (p = 0.008), indicating that a lack of physical activity negatively affects physical fitness; (3) motivation did not show a significant effect on physical fitness (p = 0.173), with external factors having higher values compared to internal factors; and (4) overall, there was a significant influence of the combination of nutritional intake, physical activity, and motivation on the level of physical fitness (p = 0.003). In conclusion, there is an influence of nutritional status, physical activity, and learning motivation on students’ physical fitness. The better the nutritional status, physical activity, and learning motivation of students, the better their level of physical fitness will be. Keywords: Elementary School Students, Learning Motivation, Nutritional Intake, Physical Activity, Physical Fitness